Guidelines for contributors (2009)
The PROFILE journal is published twice a year (April and October). It is mainly interested in sharing the results of classroom research projects undertaken by primary and secondary school teachers as well as teachers of adults while taking part in the Professional Development Programmes carried out by the Foreign Languages Department at Universidad Nacional de Colombia. It also includes articles written by teacher educators and guest teachers willing to disseminate innovations and research findings.